(p)ppGpp – an important player during heat shock response. (6th April 2023) - Driller, Kristina; Cornejo, Fabián A; Turgay, Kürşad
Abstract: The alarmones and second messengers (p)ppGpp are important for the cellular response to amino acid starvation. Although the stringent response is present in many bacteria, the targets and functions of (p)ppGpp can differ between species, and our knowledge of (p)ppGpp targets is constantly expanding. Recently, it was demonstrated that these alarmones are also part of the heat shock response in Bacillus subtilis and that there is a functional overlap with the oxidative and heat stress transcriptional regulator Spx. Here, the (p)ppGpp second messenger alarmones allow the fast stress-induced downregulation of translation while Spx inhibits the further expression of translation-related genes to lower the load on the protein quality control system, while the chaperone and protease expression is induced. In this review, we discuss the role of (p)ppGpp and its intricate connections in the complex network of stress sensing, heat shock response, and adaptation in B. subtilis cells. Abstract : In this review we discuss the interplay of stringent and heat stress response in Bacillus subtilis .